PEMANFAATAN E-BOOK PADA PLATFORM RUMAH PENDIDIKAN UNTUK PEMBELAJARAN IPAS DI KELAS V SD NEGERI 5 SULAHAN BANGLI - Dangin Cahya Lindya, Luh Gede Ayu; Suyanta, I Wayan; Suryawan, I Gde (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of digital learning media in the learning process at SD Negeri 5 Sulahan Bangli is an effort made by the school to improve the quality of science and science learning, one of which is through the use of e-books on the Rumah Pendidikan platform. The issues that will be discussed include: (1) How are e-books used on the Rumah Pendidikan platform in science and science learning in class V at SD Negeri 5 Sulahan Bangli? (2) What are the obstacles faced and what efforts are made by teachers in using e-books on the Rumah Pendidikan platform in science and science learning in class V of SD Negeri 5 Sulahan Bangli? (3) What are the implications of using e-books on the Rumah Pendidikan platform in science and science learning in class V of SD Negeri 5 Sulahan Bangli?. The theories used to analyze the problem are constructivism and behaviorism. The subjects of this research were fifth grade students. Data collection methods were through observation, interviews and documentation. The collected data was analyzed using a qualitative descriptive analysis method with reduction steps, data presentation and drawing conclusions. The research results show (1) The use of e-books on the Rumah Pendidikan platform in science and science learning in class V of SD Negeri 5 Sulahan Bangli was carried out through the planning, implementation and reflection stages. (2) The obstacles faced include internet networks, limited facilities and infrastructure, students easily lose focus and feel bored, and have difficulty seeing writing on Smart TVs. The efforts made include preparing material before learning, making maximum use of facilities and infrastructure, using a variety of learning methods, and arranging seating and viewing positions. (3) The implications of using e-books on the Rumah Pendidikan platform in science learning include increasing student interest and motivation in learning, helping students understand science material, as well as increasing student activity and involvement.